Stable isotope analysis as an indicator of tree and grass rooting depth in a mesic African savanna - Jack, Sam (Department of Biological Sciences, 2017)
This exclosure-based study in a mesic southern African savanna investigated the validity of the Walter Hypothesis, which states that trees and grasses root at different depths and subsequently exploit different soil moisture layers. Root samples were extracted from vertical soil profiles in open and under canopy cover and analysed by means of carbon nitrogen isotopes. While δ¹⁵N showed little pattern due to complexities in the fractionation process, δ¹³C revealed that tree and grass rooting depths did not adhere to separate niches as proposed by Walter (1971). Root material from both growth forms occurred throughout the profile but concentrated within the upper 20-30 cm. Significantly higher densities of tree fine roots were found under canopy cover than in the open. Grass rooting followed similar patterns in both open and canopy sites, only dominating in the upper 30 cm of the open sites. Contrary to what was expected, tree fine root density increased in the top 20 cm of the open treatment, possibly due to the lack of constraining factors such as herbivory and fire within the exclosure. It is postulated that woody cover may become increasingly dominant over time due to the relatively high rainfall in the region.